A Prototype of Multicomponent Brand Personality Structure: A Consumption Synmbolism Approach. Issue 2 (10th January 2013) - Lee, Eun‐Jung
ABSTRACT Brand personality (BP) in the postmodern marketplace encompasses a variety of anthropomorphized attributes associated with a brand, reflecting on a wide spectrum of social, cultural, and psychological associations capturing various aspects in everyday life stories of consumers. Most prior research onBP, however, has employed a psychology‐based approach, and has not yet fully demonstrated the concept's market‐driven scope in the contemporary brand schema. To bridge the gap between the practitioner and scholar, this study employed a consumption symbolism approach to develop a multicomponent structure ofBP. A qualitative study was conducted with 36 brands of six product/service categories (fashion/luxury, beverage, automotive, personal computer, cosmetics, and retailer) within a specific context (South Korea). The results yielded a prototype of multicomponent BP structure consisting of one psychological component (traits) and three sociocultural components (narratives of socioeconomic/life scene/physical variability). The findings of the study broaden the current understanding of BP by suggesting a multidisciplinary perspective embracing its sociocultural aspects, and by empirically demonstrating the prototype reflecting on a wide spectrum of consumer narratives.